Epizootiological and Epidemiological Situation on Brucellosis around the World in 2011–2020 and Forecast for the Russian Federation for 2021 - D. G. Ponomarenko; O. N. Skudareva; A. A. Khachaturova; A. N. Germanova; D. E. Lukashevich; O. V. Logvinenko; E. L. Rakitina; M. V. Kostyuchenko; D. A. Zinchenko; O. V. Semenko; O. V. Maletskaya; A. N. Кulichenko (Проблемы особо опасных инфекций, 2021)
Analysis of the incidence of human brucellosis in the world in 2011–2020 is presented in the paper. An assessment of the epizootiological-epidemiological situation on brucellosis in the Russian Federation in 2020 is performed. It is outlined that the epidemiological situation on brucellosis in Russia over the past decade was characterized as unfavorable with downward trend in the incidence rate against the background of persistent epizootiological insecurity among cattle and small ruminants. Between 2011 and 2020, 3507 first identified human cases of brucellosis were registered. The long-term average number of cases is 350 per year, including 28 cases among children under 17 years old. The average long-term intensive morbidity rate per 100 000 people was 0.24, among children under 17 – 0.1. In 2020, 119 human cases of brucellosis were detected in Russia (0.08), which indicates that the trend towards an improvement in the epidemiological situation on brucellosis continues. The largest number of brucellosis cases among people was registered in the North-Caucasian (77.1 % of the total incidence across Russia) and the Southern Federal District (13.5 %). In the period of 2010–2020 (9 months), 4610 areas potentially hazardous as regards bovine brucellosis and 422 – as regards brucellosis in sheep and goats were registered in the Russian Federation. Analysis of the development of brucellosis situation in Russia indicates that in the medium term, with the current trend maintained, there is a real risk of widespread brucellosis distribution among farm animals in the constituent entities of the Central, Volga, Far Eastern and Siberian Federal Districts, as well as the persistence of epizootiological insecurity in the North Caucasus and Southern Federal Districts. Taking into account the current epizootiological-epidemiological situation and the long-term dynamics of the development in the Russian Federation, one can predict the incidence of brucellosis in people at a level below the longterm average values – 0.13–0.18 per 100000 of the population in 2021.